Long-term survival of a patient with giant omphalocele and left congenital diaphragmatic hernia: A case report - Soma Sakamura; Shohei Honda; Takafumi Kondo; Insu Kawahara; Kazutoshi Cho; Akinobu Taketomi (Elsevier, 2024)
Introduction: The combination of a giant omphalocele (GO) and congenital diaphragmatic hernia (CDH) is extremely rare and results in high mortality and morbidity rates in neonates. The most difficult period for survival is the immediate postnatal period, with approximately one-third of newborns dying within the first 48 h after birth. Case presentation: We present the case of a newborn girl with a GO and congenital left-sided Bochdalek hernia who survived beyond the neonatal period and underwent radical surgery. The female neonate, weighing 2946 g, was delivered by scheduled Cesarean section at 37 weeks gestation. She had a left-sided Bochdalek CDH containing a small portion of the small bowel and a GO containing a large portion of the liver. There were no other associated malformations, and the pulmonary hypoplasia and pulmonary hypertension in the neonatal period were not fatal. We performed an operation to repair the diaphragmatic hernia, initially approaching it from her abdominal wall defect. We performed multiple operations to close the abdominal wall. Initially, during the neonatal period, we closed it with a skin layer; however, poor weight gain occurred afterward. Considering gastroesophageal reflux as a complication, we performed mesh-assisted abdominal wall closure and fundoplication at 10 months of age, successfully resolving the underlying disease and complications. Conclusion: Repair of the CDH from the abdominal wall defect provided good visual field and safer primary direct closure. Without using artificial materials in the CDH until closure of the GO avoided infection and resulted in a favorable outcome in this case.